1983
DOI: 10.1111/j.1151-2916.1983.tb10546.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BaO. A12O3.5TiO2 in the Ternary System BaO. A12O3‐TiO2

Abstract: A new identification and indexing for the phase BaAl2Ti5O14 were accomplished using an X‐ray diffraction technique. The new lattice parameters for the tetragonal lattice structure are: a0=9.990 × 10‐10 m and c0=12.264 × 10‐10 m, with a corresponding volume 1.224 × 10‐27 m3. The data provided by the Joint Committee on Powder Diffraction Standards are inconsistent both in lattice parameter values and Miller indices. The X‐ray powder diffraction pattern of BaAl2Ti5O14 was indexed using the LSUCR (least‐squares un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Later, Guha et al [12] reported the existence of BaO · Al 2 O 3 · 5TiO 2 which is also hexagonal. Solomah et al [13] confirmed the structural data for BaO · Al 2 O 3 · 5TiO 2 . The existence of a mineral with hollandite-type structure, having the formula BaO · Al 2 O 3 · 4 · 5TiO 2 has also been reported [14].…”
Section: Introductionmentioning
confidence: 64%
“…Later, Guha et al [12] reported the existence of BaO · Al 2 O 3 · 5TiO 2 which is also hexagonal. Solomah et al [13] confirmed the structural data for BaO · Al 2 O 3 · 5TiO 2 . The existence of a mineral with hollandite-type structure, having the formula BaO · Al 2 O 3 · 4 · 5TiO 2 has also been reported [14].…”
Section: Introductionmentioning
confidence: 64%
“…Later Guha & Kolar (1976) and Guha (1980) presented additional xrd information characterizing a new tetragonal phase 'BaAl2Ti50 14 although the two sets of data clearly had much in common (compare tables 9 and 10). Solomah et al (1983) subsequently obtained superior xrd data (table 11) and refined tetragonal lattice parameters for their own synthetic 'BaAl2Ti50 14\ Ringwood and co-workers have always described the aluminous barium endmember Synroc hollandite as BaAl2Ti60 16, whereas Vance & Agrawal (1982), and have proposed BaAl2Ti50 14 as an alternative. It would appear, however, that both these stoichiometries represent somewhat misleading oversimplifications.…”
Section: Discussion {A)mentioning
confidence: 99%
“…These calculated multiplicities are reasonably consistent with the average multi plicity of 4.98 for aluminous barium hollandites, as determined by from electron diffraction data. The d spacings listed by Solomah et al (1983), which are reproduced in table 11, are the best available for the hollandite Bax 14A12 29Ti5 710 16, and are recommended for reference purposes. These data yield a tetragonal supercell, with a = 9.977 A and c = 14.742 A (= 2.92 A x 5.05).…”
Section: Discussion {A)mentioning
confidence: 99%
See 1 more Smart Citation